Application of a weighted spatial probability model in GIS to analyse landslides in Penang Island, Malaysia. Issue 1 (2nd January 2016) - Elmahdy, Samy Ismail; Marghany, Maged Mahmoud; Mohamed, Mohamed Mostafa
Abstract : In the current study, Penang Island, which is one of the several mountainous areas in Malaysia that is often subjected to landslide hazard, was chosen for further investigation. A multi-criteria Evaluation and the spatial probability weighted approach and model builder was applied to map and analyse landslides in Penang Island. A set of automated algorithms was used to construct new essential geological and morphometric thematic maps from remote sensing data. The maps were ranked using the weighted probability spatial model based on their contribution to the landslide hazard. Results obtained showed that sites at an elevation of 100–300 m, with steep slopes of 10°–37° and slope direction (aspect) in the E and SE directions were areas of very high and high probability for the landslide occurrence; the total areas were 21.393 km 2 (11.84%) and 58.690 km 2 (32.48%), respectively. The obtained map was verified by comparing variogram models of the mapped and the occurred landslide locations and showed a strong correlation with the locations of occurred landslides, indicating that the proposed method can successfully predict the unpredictable landslide hazard. The method is time and cost effective and can be used as a reference for geological and geotechnical engineers.